Analisis Wacana Kritis Film Rudy Habibie dalam Meningkatkan Kemampuan Berpikir Kritis Mahasiswa - Goziyah, Goziyah (UNIB Press, 2019)
Discourse analysis has been noticed by several language researchers and educators over the past two decades. This study aims to analyze the use of discourse analysis on film as a medium of learning in improving students' critical thinking skills, especially in learning discourse analysis. Rudy Habibie's film is used as a medium for this analysis. The conceptual framework framework for Fairclough was adopted in this study, with a focus on analyzing meso-level critical discourse. This study explores how discursively formed in the process of production, distribution, and consumption in the film Rudy Habibie. This finding illustrates various behaviors taken from the Rudy Habibie film which aims to express stereotypes, prejudices, hegemony, power, and ideological attitudes. The ideology presented leads the audience through the film's story as a result of text production, distribution, and consumption. Representation contributes to building social strength. Furthermore, this research is believed to have implications for language teaching, especially in discourse analysis. The application of a critical discourse analysis approach in learning makes students able to understand the writer, find meaning and reason about certain writing styles and to enhance their critical thinking.